2021
DOI: 10.3389/fphar.2021.751656
|View full text |Cite
|
Sign up to set email alerts
|

Kratom Alkaloids: Interactions With Enzymes, Receptors, and Cellular Barriers

Abstract: Parallel to the growing use of kratom, there is a wealth of evidence from self-report, preclinical, and early clinical studies on therapeutic benefits of its alkaloids in particular for treating pain, managing substance use disorder, and coping with emotional or mental health conditions. On the other hand, there are also reports on potential health risks concerning kratom use. These two aspects are often discussed in reviews on kratom. Here, we aim to highlight specific areas that are of importance to give ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 77 publications
(170 reference statements)
0
18
0
Order By: Relevance
“…While average kratom dose and frequency were not higher among respondents with a psychiatric condition, other than a SUD (Grundmann, Veltri, Morcos, Knightes, Smith, Singh, et al, 2022), it is unclear how kratom may interact with other medications commonly taken among people with the conditions assessed here. Because of the potential for drug interactions, kratom consumption may lead to a higher incidence of adverse effects in patients taking a range of prescription medicines, especially medications metabolized by CYP 2D6, CYP 3A, and CYP 2C9 (Hanapi et al, 2021). Inhibition of these enzymes may increase the blood concentration of several antidepressant and anxiolytic medications that are used concomitantly with kratom in the self-treatment of psychiatric disorders.…”
Section: Beneficial and Detrimental Symptoms Of Kratom Use Centered O...mentioning
confidence: 99%
“…While average kratom dose and frequency were not higher among respondents with a psychiatric condition, other than a SUD (Grundmann, Veltri, Morcos, Knightes, Smith, Singh, et al, 2022), it is unclear how kratom may interact with other medications commonly taken among people with the conditions assessed here. Because of the potential for drug interactions, kratom consumption may lead to a higher incidence of adverse effects in patients taking a range of prescription medicines, especially medications metabolized by CYP 2D6, CYP 3A, and CYP 2C9 (Hanapi et al, 2021). Inhibition of these enzymes may increase the blood concentration of several antidepressant and anxiolytic medications that are used concomitantly with kratom in the self-treatment of psychiatric disorders.…”
Section: Beneficial and Detrimental Symptoms Of Kratom Use Centered O...mentioning
confidence: 99%
“…Additionally, to score more highly on DISCERN, online vendors could provide consumers with a broad level of understanding of how kratom works to elicit the described structure-function claims that are stipulated by DSHEA (i.e., to improve on question 9). For instance, websites can, to the extent they are able, discuss what is currently known -in lay terms -about mitragynine and 7-hydroxymitragynine, two active constituents that are known to interact with adrenergic, serotonergic, dopaminergic, and opioid receptors [30,31]. However, it should be noted that (a) not all of the pharmacology of kratom is centered on these two primary alkaloids, (b) no human studies have been conducted to examine these mechanisms, and (c) kratom is a complex botanical that cannot be simplified by merely categorizing it in traditional categories such as "opioid" or "stimulant" [32,33].…”
Section: Recommendations To Kratom Vendorsmentioning
confidence: 99%
“…A previous study conducted by Matsumoto et al (1997) had affirmed that mitragynine (1) displayed a suppressive effect on the central serotonin neurotransmission system. In mice, the suppression of 5-HT 2A agonist (5-methoxy-N, N-dimethyltryptamine)-induced head twitch response was observed due to the effect from the pre-treatment with mitragynine (1) , which showed that the principal kratom alkaloid acts as a competitive antagonist in blocking the stimulation of the 5-HT 2A receptor ( Hanapi et al, 2021 ). León et al (2021) investigated the in vitro and in vivo activity of kratom alkaloids, especially mitragynine (1) , speciogynine (2) , and speciociliatine (3) at serotonin receptors (5-HTRs).…”
Section: Pharmacology/structure Activity Relationship Study (Sars)mentioning
confidence: 99%
“…Metabolism of mitragynine (1) was first elucidated by Philipp et al (2009) . Phase I metabolism of mitragynine (1) and its diastereomers involved the hydrolysis of methyl ester of the propenoic acid at C-16 whereas O- demethylation of the methoxy group positioned at C-9 and C-17, respectively followed by oxidation or reduction reactions to form carboxylic acid or alcohol ( Hanapi et al, 2021 ). In the human liver microsomes (HLM) system, 7-hydroxymitragynine and 9- O -demethylmitragynine were discovered as the most prevalent metabolites of mitragynine (1) ( Basiliere and Kerrigan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%